Morbidity profile of 2 months-5years children according to IMNCI classification in paediatrics outpatient department of tertiary care hospital, Joka, Kolkata, India - Chaudhuri, Susmita; Dutt, Rekha; Goswami, Shweta; Benerjee, Pritam; Lahiri, Mahuya (International Journal of Research in Medical Sciences, 2017)
Background: Every year, more than 10 million children die in developing countries before they reach their fifth birthday. Seven in 10 of these deaths are due to acute respiratory infections mostly pneumonia, diarrhoea, measles, malnutrition & combination of these illnesses. The rationale of our study is to assess the profile of childhood illness in the paediatrics out- patient department at ESI-PGIMSR and MC, Joka, Kolkata, India so that the same burden can be minimised & to promote healthy upbringing of children below five years of age. Methods: This was an observational study of cross-sectional design conducted among the mother-child pair (child belonging to the age group of 2 months-5 years) visiting Pediatrics OPD during the study period i.e. 4 weeks. Convenience sampling method was used. The participants whose guardians did not give consent for the study & were seriously ill were excluded from this study. A pre-designed and pre-tested interview schedule was used. After giving a brief introduction about the topic, verbal consent was taken & face to face interview was conducted in local language. Data was compiled & computed in SPSS software version 20. Results: According to the IMNCI classification, 15.9% of the study subjects had severe pneumonia, 17.8% had pneumonia. 1.9% of the study subjects had severe dehydration. None of the respondents presented with some dehydration. Only 1% of the respondents presented with anemia. 4.9% of the respondents presented with severe malnutrition, 13.8% of them had malnutrition according to IMNCI classification.31.7% of the respondents had primary immunisation.67.3% of them had been breastfed. Among them 41.2% of them were breastfed 8 times & more a day.92% of them had supplementary feeding as rice, 33.3% of them had supplementary feeding as baby food. 69.3% of them had complained of change in food habit during illness. Conclusions: Proper counselling to parents regarding prevention of common morbidities like pneumonia, diarrhoea, malnutrition etc. should be provided at each and every possible hospital contact. Awareness about danger signs & symptoms of urgent hospitalisation should be imparted using pamphlets or other health educational materials. Health workers also should undergo proper training so that proper classification of the conditions as well as efficient management could be provided.